The theory of oxidative stress as a direct cause of cell aging - Milagros Lisset León Regal; Raúl Cedeño Morales; Rodolfo Javier Rivero Morey; Jeisy Rivero Morey; Diana Laura García Pérez; Leissay Bordón González (Medisur)
The loss of functional capacities, aging and death are inherent to all living matter due to metabolism and other factors causing the formation of substances which damage irreversibly cell structure components. With the objective of updating about the last findings which explain the role of oxidative stress on cell aging, a bibliographic review is done. It is concluded that oxygen which is necessary for cell viability and other exogenous substances show toxicity since they lead to the formation of free radicals whose action is the main cause of aging. In addition, the administration of anti- oxidants is very important to prevent aging and improve the population´s quality of life.